Peran Kecerdasan Emosional Dalam Membangun Gaya Belajar Yang Efektif: Tinjauan Dari Perspektif Pendidikan Islam - Apriliani, Widia; Muhid, Abdul (UIR Press, 2025)
This study aims to analyze the role of emotional intelligence in forming an effective learning style based on the perspective of Islamic education. Emotional intelligence is an individual's ability to understand, manage, and express emotions positively which has been proven contribute to success of learning pro-cess. On the other hand, learning style is each individual's unique preference in absorbing information either visually, auditorily, or kinesthetically. Through a qualitative approach with library study method and this research found that emotional intelligence affects students' ability to recognize their learning style, manage academic stress, and increase motivation and perseverance in learning. In the Islamic perspective, emotional intelligence is in line with values such as patience, empathy, tawakal, and sincere and is strengthened through learning that is in accordance with students' learning styles. This study emphasizes the importance of integrating emotional intelligence and learning styles that are in line with Islamic values and can create more effective, flexible, and meaningful learning.